Influence of Contrast Agent Injection Scheme Customized by Dual-Source CT Based on Automatic Tube Voltage Technology on Image Quality and Radiation Dose of Coronary Artery Imaging - He, Weiling; Chen, Xin; Hu, Rui; Sun, Wenjie; Tan, Weili (Frontiers in Surgery, 2022)
Objective To explore the influence of a contrast agent injection scheme customized by dual-source CT based on automatic tube voltage technology on coronary imaging image quality and radiation dose. Methods A total of 205 patients who underwent coronary CT angiography (CCTA) in our hospital from June 2021 to September 2021 were selected. 105 patients in the control group who underwent routine scanning according to body mass (BMI) and 100 patients in the observation group who set tube voltage and contrast agent dosage according to automatic tube voltage selection technology. CT values of the aortic root (AO); left anterior descending (LAD) branch; proximal, middle, and distal segments of the right coronary artery (RCA); and proximal and distal segments of left circumflex (LCX) branch were measured. We calculated the signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) of the image. Image quality scoring and effective dose (ED) calculation were carried out. Results There was no significant difference in the CT value, SNR value, and CNR value of each part of the artery between the two groups (P > 0.05). Image quality scores of the control group and the observation group were 1.28 ± 0.25 and 1.25 ± 0.23, respectively, and there was no significant difference in scores (P > 0.05). In the control group, the dosage of comparator was 43.81 ± 6.74 ml, and the ED was 4.92 ± 1.26 mSv. The dosage of contrast agent in the observation group was 34.23 ± 6.39 ml, and ED was 3.05 ± 0.94 mSv. The dosage of contrast agent and ED in the observation group were lower than those in the control group (P < 0.05). Conclusion The contrast agent injection scheme customized by dual-source CT based on automatic tube voltage technology can meet the clinical requirements of coronary image quality, reduce the radiation dose and contrast agent consumption, and help doctors choose a more accurate and reasonable examination scheme, which has certain clinical application value.